Quality characteristics and oxidative stabilityof chicken kavurma formulated with chicken abdominal fat as beef fat replacer - Dikici, A; Nacak, B; Yel, N; Zaimoğulları, K; İpek, G and Özer, M (Journal of the Hellenic Veterinary Medical Society, 2022)
Kavurma is a traditional cooked ready-to-eat meat product that mainly produce in Middle East countries. In kavurma formulation, main ingredients are beef/mutton meat, beef/mutton fat and salt. In this regard, fat has high influence on product’s general characteristics. Due to increasing demand on poultry products, food industry working on novel formulations include chicken meat and chicken abdominal fat. Chicken abdominal fat is an important by-product of chicken meat industry and rich in mono and polyunsaturated fatty acids. For this reason, chicken abdominal fat could be used to improve healthier products. In this study, effects of using chicken abdominal fat (CAF) in chicken kavurma formulation as partial beef fat (BF) replacer on pH, color, textural and sensorial quality and oxidative stability during cold storage (4°C) for 3 months was studied. For this purpose, one control (C: 100% BF) sample and four modified samples, P1 (87.5% BF+12.5% CAF), P2 (75% BF+25% CAF), P3 (62.5% BF+37.5% CAF) and P4 (50% BF+50% CAF), were produced. Proximate composition and texture profile analysis of samples were determined after production whereas pH, lipid oxidation parameters, color and sensory properties of samples were performed on days 0, 30, 60 and 90. Using CAF in kavurma formulations more than 25% resulted higher pH drop during storage, and resulted lower taste and general acceptability scores compared to C samples at the end of storage. P2, P3 and P4 samples had lower TBARS value compared to C during storage period probably result of antioxidative antioxidative ingredients in chicken fed. As expected, due to the semi liquid characteristic of CAF, using this fat type resulted softer products. To sum up, using CAF as BF replacer resulted lower TBARS compared to C, but it had some negative influence on sensory and quality characteristics at high ratio.